Karya Allah Atau Iblis : Analisis Teologis Atas Penyaliban Yesus Sebagai Opus Dei Berdasarkan Perspektif Injil Markus 8:31 : Penelitian - Tan Markus Setiadi Wahyu; Kosasih, Indriani; Tampubolon, Maruli Tua; Siregar, Humala Andi Aposan; Amtiran, Abdon (Lembaga Penelitian dan Pengabdian Masyarakat, 2025)
This article explores the theological paradox found in the Passion narrative of Christ as foretold in Gospel of Mark 8:31–33. The central focus of this study is to examine how the crucifixion of Jesus an event that outwardly appears to be an evil act inspired by the Devil and executed by sinful human hands can simultaneously be understood as Opus Dei, the supreme work of God for the salvation of humanity. This research applies a qualitative method using historical-critical exegesis combined with narrative theological analysis to uncover the deep theological meaning within the text. The analysis demonstrates that Mark intentionally portrays the tension between God’s sovereign redemptive plan and satanic opposition to emphasize the paradoxical character of a suffering Messiah. Through Peter, Satan attempts to divert Jesus from the path of suffering, but Jesus firmly rejects the temptation, affirming the cross as the will of the Father. Therefore, the crucifixion becomes the decisive moment where the forces of darkness are paradoxically employed by God to bring about His plan of redemption. This event embodies both Opus Diaboli and Opus Dei a point in salvation history where the greatest evil is ultimately overcome by the greatest love.